(untitled) (ARQUISUR Revista, 2024)
Urban violence becomes a global challenge, posing a significant obstacle to sustainable and equitable city development. In this context, this article offers a comprehensive analysis of the interrelation between the absence of urban planning and the focus of violence in the La Cumbre sector of Floridablanca, Santander. It qualitatively and descriptively examines four urban problem components that impact violence. Through this deep understanding of territorial and social obstacles, the aim is to provide meaningful reflections that help define the causes of violence in the urban environment. These factors may include physical aspects such as infrastructure, urban design, quality of public space, and security. This study provides a solid foundation for understanding how the community perceives and describes its territory in a more inclusive and needs–centered manner.